2022
DOI: 10.3390/app12105027
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Optimization of the Design and Process Parameters of a Hybrid DED Product Using Artificial Intelligence

Abstract: Directed energy deposition (DED) is an additive manufacturing process used in manufacturing free form geometries, repair applications, coating and surface modification, and fabrication of functionally graded materials. It is a process in which focused thermal energy is used to fuse materials by melting. Thermal effects can cause distortions and defects on the parts during the DED process, therefore they should be evaluated and taken into account during the manufacturing of products. Melting pool control and DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The inputs were the velocity, charging time, distance, and hauled part count and the output was the number of required AGVs. Pearson correlation coefficient (R) and mean absolute percentage error (MAPE) values were examined to find the best ANN structure [53]. The hidden layer included five neurons.…”
Section: Determination Of the Effect Of System Parameters On The Requ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The inputs were the velocity, charging time, distance, and hauled part count and the output was the number of required AGVs. Pearson correlation coefficient (R) and mean absolute percentage error (MAPE) values were examined to find the best ANN structure [53]. The hidden layer included five neurons.…”
Section: Determination Of the Effect Of System Parameters On The Requ...mentioning
confidence: 99%
“…The feed-forward neural network is an artificial neural network architecture, which is also called a multi-layer neural network. A feed-forward network is one in which information or signals are only sent in one direction, from input to output [53][54][55].…”
Section: Determination Of the Effect Of System Parameters On The Requ...mentioning
confidence: 99%
“…Yu et al [47] investigated the small angle detection method of bolt loosening in a wooden structure using deep learning and machine vision technology. Çallı et al [48] proposed an artificial neural network model considering the directed energy deposition (DED) process parameters. It has been shown that the proposed NN-GA is a capable method for creating topology-based geometrical patterns and process parameters for hybrid manufacturing technologies.…”
Section: Neural Network With Levenberg-marquardt and Bayesian Regular...mentioning
confidence: 99%
“…For instance, ANN models were used to predict the tensile strength of ABS P400 produced through FDM, demonstrating high accuracy in the majority of predictions [15]. Another study employed ANN techniques to create metamodels for optimizing the design parameters of hybrid components, showcasing their superior prediction capabilities compared to traditional methods like Design of Experiments (DOE) with RSM [16]. ANN models have the potential in optimizing 3D printing parameters such as layer height, thickness, fill density, temperature, and print speed for PLA materials [17].…”
Section: Introductionmentioning
confidence: 99%